1998
DOI: 10.1111/j.1439-0264.1998.tb00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Etude Morphométrique de la Paroi de la Veine Cave Caudale après Implantation d'un Filtre chez le Mouton

Abstract: The long stabilizers of the VT-LGM filter rest on large areas of the vascular wall. The morphometric study of the layers of the vascular wall, after implantation of filter in 15 ewes, divided into 3 groups of follow-up (2, 4 or 8 weeks) of 5 animals, was made at 3 levels opposite the filter and 1 level outside of it. Changes are seen for all the layers. Filter produces intimal hyperplasia. Stabilizers are quickly isolated from the blood flow. The thickness of the intimal hyperplasia grows for 4 weeks. It is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The evidence of recirculation zones and associated low " s w upstream and downstream of the captured clot do not appear to be conducive to clot dissolution, and may promote continued aggregation of blood elements, clot growth, and intimal hyperplasia. Furthermore, our computational evidence along with recent in vivo evidence 1,24,27 suggests that the total length of filter wires pressing against the vessel wall should be minimized.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The evidence of recirculation zones and associated low " s w upstream and downstream of the captured clot do not appear to be conducive to clot dissolution, and may promote continued aggregation of blood elements, clot growth, and intimal hyperplasia. Furthermore, our computational evidence along with recent in vivo evidence 1,24,27 suggests that the total length of filter wires pressing against the vessel wall should be minimized.…”
Section: Discussionmentioning
confidence: 87%
“…16 Studies have suggested the formation of intimal hyperplasia near the wall struts of the Vena Tech filter. 1,24,27 This one-stage filter has parallel wires in contact with the caval wall much like the TrapEase. Low " s w near the wires may be associated with the formation of hyperplasia observed, but more studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations